A study on the legality of abortion laws in Malaysia / Farhanna Mohd Hanif, Hartini Ramly and Sheena Alfred Jawatin - Mohd Hanif, Farhanna; Ramly, Hartini; Alfred Jawatin, Sheena (2005)
This research is conducted for the purpose of reviewing the current law on abortion. The areas that would be reviewed would be on the ambiguity of the current law of abortion in Malaysia, the exceptional situations where abortion is legal and the effectiveness of the sentencing provided by Section 312 of the Penal Code. This research would also include a pilot study that would analyze the perception of academicians and professionals in Malaysia. The rationale of choosing these individuals is to measure the responses from a well-educated people who are conscious of the laws. The result of this analysis would then be used as a ground to amend the current law and create a specific act for abortion law. The research would be conducted through library research (primary and secondary sources) and interviews. The significant contribution that can be derived from the study is that it would provide useful legal and statistical data that could provide the foundation for advance research, or, formulation of reform for the rational approach to abortion.